Entamoeba histolytica: Host parasite interactions at the colonic epithelium. Issue 1 (2nd January 2017) - Cornick, Steve; Chadee, Kris
ABSTRACT: Entamoeba histolytica ( Eh ) is the protozoan parasite responsible for intestinal amebiasis and interacts dynamically with the host intestinal epithelium during disease pathogenesis. A multifaceted pathogenesis profile accounts for why 90% of individuals infected with Eh are largely asymptomatic. For 100 millions individuals that are infected each year, key interactions within the intestinal mucosa dictate disease susceptibility. The ability for Eh to induce amebic colitis and disseminate into extraintestinal organs depends on the parasite competing with indigenous bacteria and overcoming the mucus barrier, binding to host cells inducing their cell death, invasion through the mucosa and outsmarting the immune system. In this review we summarize how Eh interacts with the intestinal epithelium and subverts host defense mechanisms in disease pathogenesis.